Analisis Soal Ujian Tengah Semester (UTS) Mata Kuliah Geometri - Nurhasanah Nurhasanah; Herlina Ahmad (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2017)
This research aims to analyze the question of the mid term exam in geometry course. Focusing on the level of difficulty, validity, and reability. This research is evalution qualitative research conducting in mathematic education departement. The quantitative data that was taken from th answer sheet of students was analyzed by using descriptive statistic. The results revealed that: (1) the level difficulty of questions number 2, 3 is very hard and 5 is hard, number 1 is average, and number 4 is low , (2) the validity of all question ( number 1 through 5 ) is valid with different level of validity, (3) the reability of questions is in average, in terms of difficulty level, most questions are difficult, it is affected the reability of the items examination that is in average level.